Integral Equations and Operator Theory - Tretter, Christiane; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser.)
Integral Equations and Operator Theory (IEOT) is devoted to the publication of current research in integral equations, operator theory and related topics with emphasis on the linear aspects of the theory. The journal reports on the full scope of current developments from abstract theory to numerical methods and applications to analysis, physics, mechanics, engineering and others. The journal consists of two sections: a main section consisting of refereed papers and a second consisting of short announcements of important results, open problems, information, etc.
Keywords: Mathematical analysis; Analysis (Mathematics).; Analysis